Nano dispersed phase reinforced Cu-Ni-based composite material and preparation method thereof
Through the design of Cu-Ni-based composite materials, combined with hot press sintering process and oxygen partial pressure control, the performance degradation of traditional copper-based electrical contacts under high temperature or high current density conditions is solved, and the comprehensive improvement of conductivity, hardness, wear resistance and fatigue resistance is achieved.
Patent Information
- Application Number
- CN202411817595.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-18
AI Technical Summary
Traditional copper-based electrical contacts are prone to grain coarsing under high temperature or high current density conditions, resulting in a decrease in mechanical properties and a decrease in fatigue resistance. The conductivity is greatly affected by impurities, making it difficult to improve the conductivity, wear resistance and fatigue resistance at the same time.
Cu-Ni-based composite material is used to form CuNi10 alloy, carbon nanotubes and nanozirconia particles. Through hot press sintering process and oxygen partial pressure control, the nano-scale dispersion state of each component is ensured, thereby improving the conductivity, hardness and wear resistance of the material.
It significantly improves the conductivity, hardness and wear resistance of electrical contacts, improves fatigue resistance, far better than pure copper materials, and is suitable for use in high loads and complex environments.
Smart Images

Figure BDA0005182246120000061 
Figure BDA0005182246120000071 
Figure BDA0005182246120000072
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of powder metallurgy materials, and in particular relates to a Cu-Ni based composite material with nano-dispersed phase reinforcement and a preparation method thereof. Background Art
[0002] In today's industrial and electronic fields, electrical contact materials play a key role in electrical equipment in terms of electrical conductivity, heat conduction and wear resistance. As a key component, powder metallurgy electrical contacts play an indispensable role in various electrical equipment and electronic products. They are widely used in switches, sockets, relays and other equipment to achieve the functions of electrical connection and current conduction. Traditional powder metallurgy electrical contacts usually use copper-based alloys as the main material because copper has good electrical conductivity. However, pure copper materials have some disadvantages, such as poor wear resistance, easy oxidation, and fast wear. Under certain working conditions, these problems may lead to a decline in the performance of electrical contacts and even affect the normal operation of the equipment.
[0003] The copper-based materials widely used at present are prone to grain coarsening under high temperature or high current density conditions, resulting in decreased mechanical properties and fatigue resistance. In order to improve the comprehensive performance of copper-based materials, traditional methods often add metal oxides or ceramic particles, such as nano-alumina to strengthen copper alloys. However, these materials are prone to agglomeration during the sintering process, resulting in uneven distribution of the dispersed phase and limited performance improvement. In addition, for copper alloys, the conductivity is positively correlated with the mean free path of electrons, which is mainly affected by the scattering effect of impurities on electrons. Any impurity element will reduce the conductivity of copper to varying degrees. Therefore, it is urgent to develop a new type of electrical contact material with high conductivity, excellent wear resistance and high fatigue resistance. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0006] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a Cu-Ni based composite material with nano-dispersed phase reinforcement.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: a Cu-Ni based composite material with nano-dispersed phase reinforcement, characterized in that: the Cu-Ni based composite material is composed of CuNi10 alloy, carbon nanotubes and nano-zirconia particles;
[0008] Calculated by mass fraction, the mass fraction of the CuNi10 alloy is 50% to 80%; the mass fraction of the carbon nanotubes is 1% to 15%; and the mass fraction of the nano zirconium oxide particles is 15% to 30%.
[0009] As a preferred solution of the Cu-Ni based composite material of the present invention, the mass fraction of the CuNi10 alloy is 70%; the mass fraction of the carbon nanotubes is 5%; and the mass fraction of the nano zirconium oxide particles is 25%.
[0010] As a preferred embodiment of the Cu-Ni based composite material of the present invention, the Cu-Ni based composite material is characterized in that it also has the following characteristics:
[0011] (i) Electrical conductivity is 76-87% IACS;
[0012] (ii) Hardness of 89 to 107 HV;
[0013] (iii) Wear rate: 0.0015~0.0031mm 3 / N·m.
[0014] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a Cu-Ni based composite material.
[0015] In order to solve the above technical problems, the present invention provides the following technical solution: comprising: preparing the mass percentage, molding, hot pressing and sintering, cooling and post-processing to obtain the Cu-Ni based composite material.
[0016] As a preferred embodiment of the preparation method of the present invention, the forming is cold pressing.
[0017] As a preferred embodiment of the preparation method of the present invention, the hot pressing sintering temperature is 800-1000° C. and the time is 1-3 hours.
[0018] As a preferred embodiment of the preparation method of the present invention, the hot pressing sintering pressure is 20 MPa.
[0019] As a preferred embodiment of the preparation method of the present invention, the oxygen partial pressure in the hot pressing sintering is 10 -3 ~10 -2 Pa.
[0020] As a preferred embodiment of the preparation method of the present invention, the hot pressing sintering is performed by vacuum control method to initially pump the gas pressure in the furnace chamber to 10 -3 Pa, and dilute the oxygen by introducing high-purity argon gas, with a gas flow rate of 50 to 300 mL / min.
[0021] As a preferred embodiment of the preparation method of the present invention, the mass fraction of hydrogen added to reduce the oxygen partial pressure during the hot pressing sintering is 0.1-1%.
[0022] Beneficial effects of the present invention:
[0023] (1) The present invention has conducted in-depth research and exploration on the electrical conductivity and wear resistance of powder metallurgy electrical contacts. In order to comprehensively improve the electrical conductivity and wear resistance, the present invention introduces carbon nanotubes and nano zirconium oxide particles as reinforcing materials. Carbon nanotubes are a nanomaterial with excellent electrical conductivity and mechanical properties, which can form a conductive network structure and improve the overall electrical conductivity of the composite material. The high electrical conductivity of carbon nanotubes makes the composite material have better electrical conductivity, thereby improving the electrical conductivity of the electrical contact. On the other hand, nano zirconium oxide has excellent hardness, wear resistance and chemical stability, as well as good electrical conductivity, which makes it an excellent alternative material and is expected to further improve the performance of the electrical contact. By replacing the traditional reinforcing phase nano alumina with nano zirconium oxide, the overall performance of the electrical contact can be improved while keeping the ratio of other materials unchanged, and its wear resistance and electrical conductivity can be improved, thereby enhancing its performance in practical applications. This design scheme of comprehensive utilization of carbon nanotubes and nano oxide particles is expected to significantly improve the performance of powder metallurgy electrical contacts. In terms of preparation process, this patent aims to combine Cu-Ni alloy and carbon nanotube nano-oxide particles to prepare a new type of composite material electrical contact to improve the performance and stability of the electrical contact. Through reasonable proportion and preparation process optimization, combined with hot pressing sintering technology and oxygen partial pressure control, it aims to achieve the nano-scale dispersion state of each component in the composite material, thereby ensuring that the performance advantages of the material are fully utilized.
[0024] (2) The present invention provides a novel preparation process for Cu-Ni based nanocomposite electrical contacts, which effectively solves the problem of uneven distribution of nano dispersed phase in CuNi10 alloy matrix and grain growth leading to performance degradation through hot pressing sintering process. This method optimizes the sintering oxygen partial pressure conditions, effectively inhibits grain coarsening, ensures uniform distribution of carbon nanotubes and nano zirconium oxide particles, and thus significantly improves the electrical conductivity and microhardness of the electrical contacts, thereby obtaining higher wear resistance and fatigue resistance. DETAILED DESCRIPTION
[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0026] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0027] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0028] Unless otherwise specified, the raw materials used in the examples of the present invention are commercially available.
[0029] Example 1
[0030] This embodiment provides a method for preparing a Cu-Ni based composite material with nano-dispersed phase reinforcement:
[0031] The invention comprises the following components by mass percentage: 70% CuNi10 alloy; 5% carbon nanotubes; and 25% nano zirconium oxide particles.
[0032] (1) The above raw materials were placed in a mechanical mixing device and mixed at a speed of 300 rpm for 120 minutes to ensure that the raw materials were evenly dispersed and fully mixed.
[0033] (2) The uniformly mixed powder is loaded into a hot pressing mold and cold pressed with an initial pressure of 12 MPa to obtain a blank.
[0034] (3) The blank is placed in a hot pressing sintering device for sintering. The specific parameters are as follows: sintering temperature 900°C; holding time 2 hours; hot pressing pressure 25 MPa; oxygen partial pressure: 10 -3 Pa, dilute oxygen with 150mL / min high-purity argon flow, and add 0.5% hydrogen to reduce the oxygen partial pressure. Use a high-precision oxygen partial pressure sensor to monitor the oxygen partial pressure in real time to ensure that the fluctuation range does not exceed ±10%.
[0035] (4) After sintering, the blank is cooled to room temperature under argon protection and then surface treated to obtain the final electrical contact product.
[0036] Example 2
[0037] The invention comprises the following components by mass percentage: 60% CuNi10 alloy; 10% carbon nanotubes; and 30% nano zirconium oxide particles.
[0038] (1) The above raw materials were placed in a mechanical mixing device and mixed at a speed of 300 rpm for 120 minutes to ensure that the raw materials were evenly dispersed and fully mixed.
[0039] (2) The uniformly mixed powder is loaded into a hot pressing mold and cold pressed with an initial pressure of 15 MPa to obtain a blank.
[0040] (3) The blank is placed in a hot pressing sintering device for sintering. The specific parameters are as follows: sintering temperature 920°C; holding time 2 hours; hot pressing pressure 30 MPa; oxygen partial pressure: 10 -2 Pa, dilute oxygen with 200mL / min high-purity argon flow, and add 1.0% hydrogen to reduce the oxygen partial pressure. Monitor the oxygen partial pressure fluctuation in real time to ensure a low oxygen environment and avoid nanophase oxidation or phase change.
[0041] (4) After sintering, the blank is slowly cooled to room temperature under argon protection, and the surface is cleaned and polished.
[0042] Example 3
[0043] The invention comprises the following components by mass percentage: 80% CuNi10 alloy; 2% carbon nanotubes; and 18% nano zirconium oxide particles.
[0044] (1) The above raw materials were placed in a mechanical mixing device and mixed at a speed of 300 rpm for 120 minutes to ensure that the raw materials were evenly dispersed and fully mixed.
[0045] (2) The uniformly mixed powder is loaded into a hot pressing mold and cold pressed with an initial pressure of 10 MPa to obtain a blank.
[0046] (3) The blank is placed in a hot pressing sintering device for sintering. The specific parameters are as follows: sintering temperature 850°C; holding time 1.5 hours; hot pressing pressure 20 MPa; oxygen partial pressure: 10 -3 Pa, dilute oxygen with 100mL / min high-purity argon flow, and add 0.2% hydrogen to reduce the oxygen partial pressure. Use a high-precision oxygen partial pressure sensor to dynamically adjust the oxygen partial pressure to ensure a stable sintering environment.
[0047] (4) After sintering, the blank is slowly cooled to room temperature under argon protection, and the surface is cleaned and polished.
[0048] Comparative Example 1
[0049] Pure copper powder (particle size of 10-50 μm) is used as raw material without adding any reinforcing phase material. The pure copper powder is loaded into a hot pressing mold and cold pressed to obtain a blank. The blank is hot pressed and sintered. The sintering process parameters are as follows: sintering temperature 900°C; holding time 2 hours; hot pressing pressure 20 MPa; oxygen partial pressure is controlled at 10 by inert gas flow rate. -2 Pa, the inert gas flow rate is set to 150 mL / min. After sintering, it is cooled to room temperature under the protection of inert gas to obtain pure copper electrical contact material.
[0050] Comparative Example 2
[0051] The difference from Example 3 is that the CuNi10 alloy is replaced by pure copper as the base material. Specifically, the CuNi10 alloy powder (80%) is used in Example 3, while the pure copper powder (100%) is used as the base material in the comparative example, and other conditions remain the same.
[0052] Comparative Example 3
[0053] The difference from Example 1 is that the following components are included in terms of mass percentage: 50% CuNi10 alloy; 18% carbon nanotubes; 32% nano zirconium oxide particles, and other conditions remain the same. Result: Not sintered densely, performance cannot be measured
[0054] CuNi10 alloy, as a copper-nickel alloy, generally has good sintering properties. Copper itself has good sintering properties at high temperatures, so CuNi10 alloy can achieve good densification during hot pressing sintering. According to the hot pressing sintering process used in Example 1 (sintering temperature 900°C, holding time 2 hours, hot pressing pressure 25MPa, oxygen partial pressure controlled at 10 -3 Pa), this process is helpful to improve the densification of CuNi10 alloy under reasonable temperature and pressure, and controlling the oxygen partial pressure can effectively inhibit the oxidation of carbon nanotubes.
[0055] Nano-zirconia particles generally have a higher melting point (about 2680°C) and usually exist as a reinforcing phase. Nano-zirconia particles do not participate in liquid phase sintering, so they do not directly affect the density of the matrix material during sintering, but they may promote the uniform dispersion of the material, thereby improving the properties of the material after sintering. However, a higher proportion of zirconia particles (32%) may affect the overall sintering density because the interfacial bonding strength between them and the matrix is low, which may lead to the presence of pores at the interface.
[0056] The presence of carbon nanotubes will affect the sintering density. Carbon nanotubes usually show a strong tendency to agglomerate at high temperatures due to their higher surface energy, which may cause uneven dispersion during the sintering process and affect the overall density of the material. In order to avoid oxidation of carbon nanotubes during the sintering process, the stability of the carbon nanotubes is ensured by controlling the low oxygen partial pressure in the embodiment, which helps to maintain its dispersion and reduce agglomeration, thereby reducing the negative impact on densification. However, due to the high proportion of carbon nanotubes (18%), this may pose certain challenges to sintering density, because carbon nanotubes will produce gaps, resulting in reduced density in local areas.
[0057] The materials obtained from Examples 1 to 3 and the comparative example were tested. The test methods are shown in Table 2, and the results are shown in Table 3.
[0058] Table 2
[0059]
[0060]
[0061] Table 3
[0062]
[0063] The embodiment of the present invention has an improvement of 122.22% in hardness and 212.5% in wear resistance compared to comparative example 1. The pure copper electrical contact material has advantages in electrical conductivity, but its hardness, wear resistance and fatigue resistance are poor, and it is difficult to meet the use requirements of high loads and complex environments. The Cu-Ni-based nanocomposite electrical contact material of the present invention achieves comprehensive optimization of performance through the introduction of nano-reinforced phases and precise control of oxygen partial pressure, and is far superior to pure copper materials in terms of mechanical properties and durability, showing significant technical advantages and application prospects.
[0064] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A Cu-Ni based composite material with nano-dispersed phase reinforcement, characterized in that: The Cu-Ni based composite material is composed of CuNi10 alloy, carbon nanotubes and nano zirconium oxide particles; Calculated by mass fraction, the mass fraction of the CuNi10 alloy is 50% to 80%; the mass fraction of the carbon nanotubes is 1% to 15%; and the mass fraction of the nano zirconium oxide particles is 15% to 30%.
2. The Cu-Ni based composite material according to claim 1, characterized in that: The mass fraction of the CuNi10 alloy is 70%; the mass fraction of the carbon nanotubes is 5%; and the mass fraction of the nano zirconium oxide particles is 25%.
3. The Cu-Ni based composite material according to claim 1 or 2, characterized in that: It also has the following features: (i) Electrical conductivity is 76-87% IACS; (ii) Hardness of 89 to 107 HV; (iii) Wear rate: 0.0015~0.0031mm 3 / N·m.
4. The method for preparing the Cu-Ni based composite material according to claims 1 to 3, characterized in that: The method comprises the steps of mixing, molding, hot pressing, sintering, cooling and post-processing the mass percentage according to any one of claims 1 to 2 to obtain the Cu-Ni based composite material.
5. The preparation method according to claim 4, characterized in that: The forming is cold press forming.
6. The preparation method according to claim 4, characterized in that: The hot pressing sintering temperature is 800-1000° C. and the time is 1-3 hours.
7. The preparation method according to claim 6, characterized in that: The hot pressing sintering pressure is 20 MPa.
8. The preparation method according to claim 6, characterized in that: The oxygen partial pressure in the hot pressing sintering is 10 -3 ~10 -2 Pa.
9. The preparation method according to claim 8, characterized in that: The hot pressing sintering process uses a vacuum control method to initially pump the gas pressure in the furnace chamber to 10 -3 Pa, and dilute the oxygen by introducing high-purity argon gas, with a gas flow rate of 50 to 300 mL / min.
10. The preparation method according to claim 9, characterized in that: The mass fraction of hydrogen added during the hot pressing sintering to reduce the oxygen partial pressure is 0.1-1%.